Evaluation of Modified Asphalt Binder and Mixtures with Polyphosphoric Acid - Hilal, Miami (Al-Nahrain Journal for Engineering Sciences, 2023)
Rutting is the most common distress that most Iraqi asphalt pavements suffer from it. Asphalt binders are modified by using additives and polymers to enhance their physical qualities and fulfill the performance demands. Polyphosphoric acid (PPA) has been used in many countries to enhance the physical and mechanical characteristics of asphalt binders and mixtures that can improve the performance of asphalt pavements. In this paper, evaluation of the Iraqi asphalt binder and mixtures performance by using three percentages of Polyphosphoric acid (PPA) (0.4, 0.8, and 1.2) percent by asphalt binder weight and added to (60-70) penetration grade asphalt binder to show the applicability and suitability of using PPA in asphalt pavement in Iraq. Original asphalt binder and modified are subjected to traditional tests which are penetration, ductility, softening point, and viscosity. Results show better performance and enhancement of the physical properties of the modified binder. Other tests are Marshall Stability and wheel track tests. The results of the addition of PPA to the asphalt mixture show increases in the Marshall Stability and enhance the performance of the asphalt pavement mixtures. The wheel track test is applied to the original and modified mixture at two test temperatures 40 ?C and 50 ?C and the results show a decrease in the rut depth when the percentages of PPA increase. It is concluded that %PPA addition will enhance the performance of the Iraqi asphalt pavement and the mixture will be more rutting resistant, especially in high-temperature weather.